(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Hemida M, Mulyana B, Vityi A. 2022. Determinant of farmers’ participation and biodiversity status in the program of agroforestry rehabilitation in Sudan. Biodiversitas 23: 5638-5645. The agroforestry Rehabilitation Program (ARP) was launched in Nabag Reserve Forest (NRF), Sudan, to rehabilitate the forest cover and improve livelihoods for communities around the forest. To enhance the efficacy of such rehabilitation programs, it is crucial to understand the impact of various factors on community perception of participation in forest rehabilitation. The objectives of this study were to (i) examine the factors that influence farmers’ perceptions of their involvement in the program and (ii) assess the biodiversity of trees and crop species in the program. Data was gathered through a survey that included personal interviews with 200 farmers who participated in the program. A total of 250 circular sample plots were established randomly to achieve the second objective. The results showed that extension services, farming experience, family members, educational level, land size, and gum Arabic production positively influence farmers’ perceptions. The study findings identified nine tree species and five crop species in NRF. The dominant tree species were Acacia senegal and Balanites aegyptiaca which represented 62.8% and 12.4 % of the total species, respectively. At the same time, groundnut and watermelon were identified as favorite crops cultivated by farmers. Furthermore, the non-rehabilitated area has shown better value in richness, heterogeneity, and evenness than the rehabilitated areas.